PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA PADA SISWA KELAS V SD UNISMUH MAKASSAR - Nurul Febrianti, Dilla; Azis, Abdul; Gustaf Said, Try (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Based on observations at Lab School SD Unismuh Makassar, the learning process conducted by teachers, especially in the fifth-grade Pancasila Education class, showed relatively low learning outcomes. This condition occurred because teachers tended to use limited learning media, such as picture media, without actively involving students in the learning process. To overcome this problem, it is necessary to apply a learning model that can improve students’ learning outcomes, namely the Problem Based Learning model. This learning model encourages students to think critically, solve problems, and actively participate in the learning process. This study aimed to determine the effect of the Problem Based Learning model on the learning outcomes of fifth-grade students in Pancasila Education at SD Unismuh Makassar. The results of the study showed that the average score of students’ learning outcomes in the pretest was 58.05 and increased to 76.36 in the posttest, indicating an improvement in students’ learning outcomes. The hypothesis test results showed that the significance value obtained was 0.000, which is smaller than the significance level of 0.05 (0.000 < 0.05). Based on these results, H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that the Problem Based Learning model has a significant effect on the Pancasila Education learning outcomes of fifth-grade students at SD Unismuh Makassar.